Weighted composition operators between different fock spaces - Tien, Pham Trong (2019)
We study weighted composition operators acting between Fock spaces. The following results are obtained: (i) Criteria for the boundedness and compactness. (ii) Characterizations of compact differences and essential norm. (iii) Complete descriptions of path connected components and isolated points of the space of composition operators and the space of nonzero weighted composition operators.